Improvement of Renal Function after Pyeloplasty Determined by 99mTc DTPA Renogram - Misbah, Tanbir Al; Chowdhury, ATM Mowladad; Enayetullah, Imtiaz; Shahriar Ahmed, Abul Bashar (Bangladesh Journal of Urology, 2022)
Objective: To evaluate the improvement of renal function after pyeloplasty measured by 99mTc-DTPA renography. Materials and Methods: This hospital based quasi experimental study was done in the department of urology, National Institute of Kidney Diseases and Urology (NIKDU) and Bangladesh Institute of Research and Rehabilitation for Diabetes, Endocrine and Metabolic Disorders (BIRDEM) from July 2014 to December 2020. Sixty patients were included in this study who underwent Anderson-Hynes (A-H) dismembered pyeloplasty for pelviureteric junction (PUJ) obstruction. All patients were evaluated with diuretic 99mTc- DTPA renogoam before and at 3 and 6 months after operation. Improvement of renal function was evaluated by comparing preoperative and postoperative differential renal function (DRF) and glomerular filtration rate (GFR). Results: Sixty patients with unilateral hydronephrosis due to PUJ obstruction were included in this study. Of these patients 34 male and 26 female with mean age of 15.6 years (ranged from 3 – 38 years). Out of 60 patients, 56.7% had left sided hydronephrosis and 43.3% had right sided hydronephrosis. Diuretic renography was done using 99mTc- DTPA in all patients preoperatively and at 3 and 6 months postoperatively. Preoperative mean DRF and GFR were compared with post-operative findings. The mean preoperative DRF in the study was 16.72 ± 8.35% at baseline which increased to 26.03 ± 7.08% at the end of 3rd month and 28.15 ± 5.84% at the end of 6th month. The mean preoperative GFR was 14.29 ± 6.73 ml/min/1.73 m2 at baseline which increased to 24.13 ± 5.31ml/min/ 1.73 m2 at the end of 3rd month and 27.38 ± 4.78 ml/min/1.73 m2 at the end of 6th month. Conclusion: The result demonstrates that, after pyeloplasty renal function improves. Highest recovery of renal function occurs in children and patients with poor pre-operative DRF and GFR. Bangladesh J. Urol. 2021; 24(2): 155-160